Akhlaq Education Model in Kuttab An-Nubuwwah Sukabumi - Rubi Babullah; Siti Qomariyah; Siti Ulfah; Ujang Natadireja; Neneng Nur (At-Tasyrih: jurnal pendidikan dan hukum Islam, 2023)
The Kuttab An-Nubuwwah education system is an education system inspired by kuttab education in classical times. Kuttab is an educational institution that has a long history. The emergence of this education system is expected to be able to answer the needs of society, especially Muslims towards improving the quality of life in line with Islamic teachings and in accordance with the times. The formulation of the problems in this study include: (1) What is the educational model of the kuttab system implemented at Kuttab An-Nubuwwah? (2) What is the specialty of moral education with the kuttab system in Kuttab An-Nubuwwah? (3) What are the supporting and inhibiting factors in implementing moral education at Kuttab An-Nubuwwah?. In order to answer the formulation of the problem, the researcher uses a type of field research (field research) which is descriptive qualitative in nature. Based on the results of the study, it was concluded that the kuttab system educational model applied in An-Nubuwwah kuttab is an educational model that focuses on mastery of Al-Qur`an and Faith material in accordance with the intellectual level of the students. The curriculum used is the local curriculum which includes Al-Qur`an, Faith, and General Subjects (MPU). The approaches used include exemplary approaches (uswatun hasanah) and habituation. The learning methods used are talaqqi, tasmi', murojaah, lectures, questions and answers, stories, parables, and others. The evaluation used in Kuttab An-Nubuwwah is a test in written and oral form including memorization tests, formative tests and summative tests. The supporting and inhibiting factors in the implementation of education in this kuttab are the facilities and infrastructure, the number of students in each halaqah, teachers and parents.